Propuesta arquitectónica para un centro de recreación y deporte (Aipe,Huila) (2020)
The following thesis investigation. Its purpose is to achieve and organize recreational and sports places for the population of the municipality of aipe , where we can carry out different activities, the problem stems from the lack of spaces for healthy total recreation. Aipe currently has a central park, there is a recreational and sports center made up of an extensive architectural program.